Inhibitory effect of Trichoderma spp. Causing Green Mold Disease on the Edible Mushroom Pleurotus pulmonarias' and Pleurotus floridanus - Shan Wan Swan; Fasehah Mohd Mulana; Jaya Seelan Sathiya Seelan; Tan Yee Shin (Universiti Kebangsaan Malaysia, 2025)
The popular cultivated edible oyster mushrooms in Malaysia, Pleurotus pulmonarias' (grey oyster mushroom) and Pleurotus floridanus (white oyster mushroom), are susceptible to green mold disease caused by Trichoderma spp. The decline of the quality and yield production of the mushrooms up to 100% has been frequently observed due to infection by Trichoderma. The objective of this study was to investigate the competitive inhibition of Trichoderma spp. isolated from the farm with Pleurotus spp. Nine strains of Trichoderma were cultured in vitro with Pleurotus on potato dextrose agar and the radial growth as well as mycelial diameter growth were recorded. The direct plate assay results showed that T. koningiopsis and T. harzianum were the most pathogenic strains against P. pulmonarias' and P. floridanus by overgrowing and replacing the mycelia, respectively, due to space competition and nutrient suppression. The bi-plate Petri dish approach for assessing contactless inhibition of Trichoderma spp. against Pleurotus spp. demonstrated that T. asper Ellum, T. ghanense, and T. koningiopsis were able to cross over the partition and inhibit P. pulmonarias' mycelium. Meanwhile, inverted plate assay demonstrated that T. ghanense and T. reesei inhibited P. pulmonarias' mycelia, respectively, indicating contactless inhibition of Pleurotus by Trichoderma. When tested with P. floridanus, only T. ghanense demonstrated inhibition in bi-plate Petri dish method and inverted plate assay. In summary, all nine Trichoderma spp. suppressed Pleurotus growth in varying degrees. Thus, besides competing with mushroom mycelia for nutrients and space, Trichoderma sp. could also release volatile organic compounds that act without direct contact.